Effect of BaTiO3 Nanopowder Concentration on Rheological Behaviour of Ceramic Inkjet Inks. (April 2015) - Kyrpal, R; Dulina, I; Ragulya, A
Abstract: The relationship between rheological properties of ceramic inkjet inks based on BaTiO3 nanopowder and solid phase concentration has been investigated. In the ink volume takes place the formation periodic colloidal structures (PCS). The determining factor of structure formation is powder-dispersant ratio. Structural constitution of in the system with the low pigment concentration represented as PCS2, that contains solid particles in deflocculated that stabilized by the presence of adsorption-solvate layers. Dilatant structure formation for such inks explained by constrained conditions of the interaction. Samples with high BaTiO3 concentration have been classified as PKS1 . Dilatant properties of the PKS1 resulted in particles rearrangement under the influence of the flow. In the region of some values powder-dispersant ratio take place conversation PKS2 to PKS1 and ink structure transformation from monodisperse to aggregate state.